Asset and Liability Management Strategy in Islamic Banking: Strategi Manajemen Aset dan Liabilitas Dalam Perbankan Syariah - Tri Hapsari, Annisa; Sari, Nurma; Amelia Putri, Novi (LPPM UPMI, 2023)
In the company there are two sides to be balanced ie assets and liabilities Where the company should be able to give good profit and minimize the risks that exist and able to cover existing obligations as well as with Islamic banks, should be able to optimize and memgelola sources of funds effectively and efficiently such as: Increase in deposits segmentation (dpk, Strengthening corporate segmentation to increase revenue, Increased fee-based income, Increasing the role of regulator, an increase in the accountability system, As for the ALMA strategies used by Islamic banks is planning, funds management and Quality Management Financing. Strategy ALMA also able to minimize risks such as: Financing risk, Liquidity risk, pricing risk, Foreign exchange risk, Contingent risk, liquidity risk, Gap risk.